2023
DOI: 10.3389/fendo.2023.1144393
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial proteomic profile of patients with repeated implantation failure

Jing Yang,
Linlin Wang,
Jingwen Ma
et al.

Abstract: IntroductionSuccessful embryo implantation, is the initiating step of pregnancy, relies on not only the high quality of the embryo but also the synergistic development of a healthy endometrium. Characterization and identification of biomarkers for the receptive endometrium is an effective method for increasing the probability of successful embryo implantation.MethodsEndometrial tissues from 22 women with a history of recurrent implantation failure (RIF) and 19 fertile controls were collected using biopsy cathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Specifically, the iTRAQ analysis revealed that the expression of the proteins HSD17B2 and AZGP1 decreased in samples from patients with RIF compared to those of the control group, while the proteins TPPP3, APEX1, and S100A13 showed increased expression in the RIF group. The results from Western blot and immunohistochemistry showed that the levels of TPPP3, HSD17B2, S100A13, and AZGP1 were significantly reduced in the endometrium of patients with RIF [20].…”
Section: Comparison Of Protein Expression In Endometrial Tissue Sampl...mentioning
confidence: 96%
“…Specifically, the iTRAQ analysis revealed that the expression of the proteins HSD17B2 and AZGP1 decreased in samples from patients with RIF compared to those of the control group, while the proteins TPPP3, APEX1, and S100A13 showed increased expression in the RIF group. The results from Western blot and immunohistochemistry showed that the levels of TPPP3, HSD17B2, S100A13, and AZGP1 were significantly reduced in the endometrium of patients with RIF [20].…”
Section: Comparison Of Protein Expression In Endometrial Tissue Sampl...mentioning
confidence: 96%